2021
DOI: 10.1016/j.isci.2021.103168
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific N-glycosylation of integrin α2 mediates collagen-dependent cell survival

Abstract: Summary Integrin alpha 2 (ITGA2) promotes cancer metastasis through selective adhesion to ECM proteins; however, the specific contribution of integrin glycosylation remains uncertain. We provide evidence that ITGA2 is a highly glycosylated transmembrane protein expressed in ovarian cancer tissue and cell lines. In-depth glycoproteomics identified predominant N - and O -glycosylation sites harboring substantially divergent ITGA2 glycosylation profiles. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Based on the exo-protein markers identi ed with the work ow we employed, we were able to narrow down the markers to seven proteins namely, ACSL4, IGSF8, ITGA2, ITGA5, ITGB3, MYOF and STX4. Previous studies on protein levels of these markers have shown that ACSL4, ITGA5 and STX4 are highly upregulated in ovarian cancer tissues [52][53][54] , while ITGA2 was upregulated in omental tumors 55 . High protein expression levels of ACSL4, ITGA2 and ITGA5 have been implicated in poor prognosis 52,53,56 ; however, the low expression of ITGB3 in HGSOC has been associated with favorable prognosis 57 .…”
Section: Discussionmentioning
confidence: 93%
“…Based on the exo-protein markers identi ed with the work ow we employed, we were able to narrow down the markers to seven proteins namely, ACSL4, IGSF8, ITGA2, ITGA5, ITGB3, MYOF and STX4. Previous studies on protein levels of these markers have shown that ACSL4, ITGA5 and STX4 are highly upregulated in ovarian cancer tissues [52][53][54] , while ITGA2 was upregulated in omental tumors 55 . High protein expression levels of ACSL4, ITGA2 and ITGA5 have been implicated in poor prognosis 52,53,56 ; however, the low expression of ITGB3 in HGSOC has been associated with favorable prognosis 57 .…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, we found that the methylation levels of 3 genes ( ITGA2 , CST9 , and ZIM2 ) in cfDNA are associated with the abovementioned imbalance of T-cell differentiation in this study. Integrin alpha 2 (ITGA2, CD49b) is the alpha subunit of a transmembrane receptor that mediates signal transduction within the cell–cell and cell–extracellular matrix (ECM) interactions, which play roles in various cell functions [ 27 , 28 ]. As a cell signal transduction receptor [ 29 , 30 ], ITGA2 forms T-cell immune synapses to activate T-cells and regulate their proliferation, cytokine secretion [ 31 ], and apoptosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ST6Gal1 sialylation of β1 integrin in colon cancer also enhanced radio-resistance ( Lee et al, 2008 ). Furthermore, in the ovarian cancer line OVCAR4, ST6Gal1-mediated α2,6 sialylation was essential for integrin α2-dependent cancer cell survival ( Huang et al, 2021 ). In an in vivo model of mice mammary carcinoma, decreased cancer differentiation was observed with elevated ST6Gal1 and β1-integrin ( Hedlund et al, 2008 ).…”
Section: St6gal1 and Neoplastic Pathwaysmentioning
confidence: 99%